Population of Razor Clams (Family Solenidae and Family Pharidae) at Bako and Buntal, Sarawak - Tan, Chee Yong (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study was carried out primarily to assess and gather preliminary data on the availability of razor clams in Kuching Bay, Sarawak; namely in Bako and Buntal. There was a variety of razor clam species found, mainly under the Family Solenidae and Family Pharidae. They included Solen regularis, Solen sarawakensis, Solen digitalis, and unidentified "ambal goyang" and "ambal celapa" that collected by line transects method. Solen regularis was relatively more abundant and dominant compared to other species (such as S. digitalis and S. sarawakensis). In addition, this study was designated to determine the distribution pattern, species density, size and species composition between both study sites. The results showed that density of razor clams were higher at the high tide but decreased towards low tide area, while bigger sample sizes were found towards low tide area. Moreover, the highest density of individual was found at Tabo, Buntal while the lowest was recorded at Batu Sepit, Bako. On the other hand, correlation analysis of size composition and several physico-chemical parameters with the number of individual have been done.